2014
DOI: 10.5897/ajar2013.8300
|View full text |Cite
|
Sign up to set email alerts
|

Performance of wheat (Triticum aestivum L.) crop under different spacings of trees and fertility levels

Abstract: A field experiment was laid out at Pantnagar (Uttarakhand, India) in Mollisols during rabi season (2009-10) to study effect of spacing and fertility levels on growth and yield of wheat (Triticum aestivum L.) under different tree species in Terai region. The experiment was conducted in split-split plot design comprising four tree species in main plots, four spacing treatments in sub plots and four fertility levels in sub-sub plot with three replications. The wheat crop var. PBW-502 was sown on November 29, 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Diffuse light promotes the establishment of vegetative structures in agroforestry systems, whereas intense light favors the growth of flowers, fruits, and seeds. On the other hand, [28] observed comparable results and suggested that leaf litter inputs from agroforestry trees may provide appropriate nutrients and organic matter to support crop growth, possibly boosting plant height of broccoli.…”
Section: F Yield Contributing Parameters Of Broccolimentioning
confidence: 79%
“…Diffuse light promotes the establishment of vegetative structures in agroforestry systems, whereas intense light favors the growth of flowers, fruits, and seeds. On the other hand, [28] observed comparable results and suggested that leaf litter inputs from agroforestry trees may provide appropriate nutrients and organic matter to support crop growth, possibly boosting plant height of broccoli.…”
Section: F Yield Contributing Parameters Of Broccolimentioning
confidence: 79%
“…To achieve this, various coverings, such as sieved soil, sand, rice hulls, or pine needles, can be utilized to keep the seeds moist. It is crucial, however, not to add supplementary fertilizer to the substrate, as this could elevate the risk of diseases like dampingoff [59,81,89,90].…”
Section: Controlling Germinationmentioning
confidence: 99%
“…Consequently, a substrate devoid of fertilizer, like sand, is generally deemed an ideal germinating medium. Small seedlings are particularly prone to damping-off, a condition caused by fungi present on the seed surface or in the substrate [59,81,89,90].…”
Section: Controlling Germinationmentioning
confidence: 99%
“…"In India, rice and wheat are the most important cereal crops of Kharif and Rabi seasons, respectively" [1,2,3]. Rice and Wheat are considered to be major staple food crops for the majority of India's population [4].…”
Section: Introductionmentioning
confidence: 99%